HUBUNGAN CITA RASA DENGAN SISA MAKANAN BIASA PADA PASIEN RAWAT INAP DI RUMAH SAKIT TK II UDAYANA DENPASAR - Ni Komang Desi Dina Purwita; Desak Putu Sukraniti; Ida Ayu Eka Padmiari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2023)
Food maintenance is the responsibility of Nutrition Installation at Tk. II Udayana Hospital Denpasar, but often find problems in the form of patient food waste that exceeds the standard. This study aims to analyze the relationship of taste with ordinary food waste in the hospitalization at Tk. II Udayana Hospital Denpasar, as one of the scientific evaluation steps in reducing food waste. The data in this study were collected by questionnaire and observation methods. The results of this study showed that the results showed that, of the 47 samples studied that had a large sample food waste is 18 people (38.3%), which is classified as a small number of 29 people (61.7%) and averaged the sample regular food waste of 18.4%. The sample that stated the taste of good food was 42 people (89.4%) and stated the taste of food is not good ie 5 people (10.6%).Keywords: Flavor,Food wasted